2010
DOI: 10.1243/09544119jeim901
|View full text |Cite
|
Sign up to set email alerts
|

Relative influence of surface topography and surface chemistry on cell response to bone implant materials. Part 2: Biological aspects

Abstract: A current medical challenge is the replacement of tissue which can be thought of in terms of bone tissue engineering approaches. The key problem in bone tissue engineering lies in associating bone stem cells with material supports or scaffolds that can be implanted in a patient. Beside bone tissue engineering approaches, these types of materials are used daily in orthopaedics and dental practice as permanent or transitory implants such as ceramic bone filling materials or metallic prostheses. Consequently, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
164
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(180 citation statements)
references
References 182 publications
(278 reference statements)
3
164
0
13
Order By: Relevance
“…The nano-topography on Ti-SLA results from the etching process that was originally performed to eliminate corundum particles that remained on the titanium surface after blasting. A great number of studies were recently focused on the preparation of tailored nanotopographies on titanium and to the characterization of the influence of these nano-topographies on the biological response in vitro and in vivo (reviewed in [10,27]). Although the effect cannot fully be explained yet, it seems that nano-topography-based effects are more pronounced in the early stages of osseointegration.…”
Section: In Vivo Studymentioning
confidence: 99%
“…The nano-topography on Ti-SLA results from the etching process that was originally performed to eliminate corundum particles that remained on the titanium surface after blasting. A great number of studies were recently focused on the preparation of tailored nanotopographies on titanium and to the characterization of the influence of these nano-topographies on the biological response in vitro and in vivo (reviewed in [10,27]). Although the effect cannot fully be explained yet, it seems that nano-topography-based effects are more pronounced in the early stages of osseointegration.…”
Section: In Vivo Studymentioning
confidence: 99%
“…The cell is also very sensitive to the traction caused by surface morphology and hardness of biomaterials, which confirming that even a small stress can also affect the differentiation of stem cell [29][30][31]. It was reported that stem cells commit to the directly differentiation lineage specified by matrix elasticity, which was differentiated into nerve cells with the elastic modulus from 0.1 to 1 KPa, muscle cell with 8 -17 KPa interval, and osteoblast with 25 -40 KPa [1].…”
Section: The Effect Of Mechanical Propertiesmentioning
confidence: 77%
“…Для уточнения особенностей клеточной экспансии Рис. 6 Клеточная популяция образца тканеин-женерного эквивалента костной ткани на основе биорезорбируемых синтети-ческих полимерных клеточных матриц на 3-и сут после заселения, ув. 20; свето-оптическая микроскопия, инвертирован-ная микроскопия …”
Section: рисunclassified
“…Результаты дан-ных работ свидетельствуют о том, что, наряду с микровключениями и микро-порами, важную роль при создании искусственной костной ткани игра-ют нановключения, нанопоры [6,17,19]. Подобный подход, с нашей точки зрения, позволит увеличить биосов-местимость создаваемых импланта-тов и оказать влияние на клеточные реакции, связанные с дифференци-ровкой и ростом.…”
unclassified